IMPLEMENTASI KEBIJAKAN PUNGUTAN PAJAK HOTEL KATEGORI RUMAH KOS DI KOTA MANADO PROVINSI SULAWESI UTARA - RADANGKILAT, REYNE IVONE; PIO, RIANE; TAMPI, JOHNY (Sam Ratulangi University, 2018)
The implementation of public policy is something that is complex, involving various actors, parties, relatedto the environment or the context in which the policy is to be implemented to achieve its objectives. In thisregard, the existence of various models used to see how policies are implemented that are associated withthat goal is not to measure the extent to which policies have been implemented to achieve their objectives.Based on the problems raised, this study was designed using a qualitative approach. Researchers chose thecity of Manado as the location of the study; this was because in this city there was clearly a growth inboarding houses. Based on the analysis based on the theory of policy implementation by Van Meter andVan Horn, the Implementation of Hotel Taxation Policy Category of Kos Houses in Manado City, NorthSulawesi Province has not gone well. This research suggests: socialization and affirmation to staff aboutactivities that are part of the work program and field duties; staff and operational funds are developed;compile SOPs for the implementation of tasks, both at the subfield level and at the field level; follow up onstaff who do not carry out their duties properly and taxpayers who are not tax conscious; and conductfurther analysis on the lack of legislative support in the hotel tax collection policy for boarding houses.Keywords: Implementation, Kos House Tax